LEADERSHIP OF THE SCHOOL PRINCIPLE IN MANAGING THE ADIWIYATA PROGRAM - Iwan KISWANTO (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2022)
This article aims to analyze the leadership of the principal in managing the Adiwiyata program in terms of the rules used at SDN Sangiang Jaya. To analyze the principal's leadership competence in managing the Adiwiyata program at SDN Sangiang Jaya. Analyzing the process of forming a superior Adiwiyata program in the scope, school activities, work procedures and social interaction at SDN Sangiang Jaya. Analyzing the environmental conditions of the principal's leadership in managing the Adiwiyata program at SDN Sangiang Jaya. Analyzing the quality of the principal's leadership work in managing the Adiwiyata program at SDN Sangiang Jaya. This research method is a qualitative description with the content analysis approach, data collection with observation of participation, in -depth interviews and documentation. The results of the study are 1. Analyze the leadership of the principal in managing the Adiwiyata program in terms of the rules used at SDN Sangiang Jaya, 2 analyzed the principal's leadership competency in managing the Adiwiyata program at SD NEGERI SANGIANG JAYA.3 Analyzing the process of forming the Adiwiyata Superior program in the scope, School activities, work procedures and social interaction at SDN Sangiang Jaya. 4. Analyze the environmental conditions of the principal's leadership in managing the Adiwiyata program at SDN Sangiang Jaya. 5. To analyze the quality of the principal's leadership work in managing the Adiwiyata program at SDN Sangiang Jaya. So the leadership of the Principal at SD Negeri Sangiang Jaya in managing the Adiwiyata program is in accordance with the applicable rules.